Remitting seronegative symmetrical synovitis with pitting edema and polymyalgia-like syndromes following cancer immunotherapy with checkpoint inhibitors: causal link, potential association or else? - Ciro Manzo (Beyond Rheumatology, 2021)
Dear Editors,